The Pre-Medical Health Coach (PHC) program: pre-medical students as volunteer health coaches at a safety-net hospital in California, 2016–2020 - Emma B. Shak; Lyn Berry; Bryant Chow; Sharone Abramowitz; Kala M. Mehta (BMC Medical Education)
Abstract Background The volunteer Pre-Medical Health Coach (PHC) program engages student volunteers, in team-based primary care providing self-management support to patients with chronic conditions. Both the PHCs and the patients they serve are diverse. The aims of this study are to assess the impact of the PHC program on student outcomes and patient biomarkers. Methods All PHCs were students recruited from local universities, interviewed, then trained in motivational interviewing and evidence-based chronic disease self-management support. The 22 PHCs were diverse – 8 (36.3%) were underrepresented in medicine and 2 (9%) were first generation in college. The study setting was a public safety-net adult medicine outpatient clinic in Oakland, California. PHCs spent 5 h weekly, for 1–3 years, volunteering alongside primary care residents and faculty. Duties included: (1) observing the doctor-patient interview, (2) on-site health coaching, and (3) telephone follow-up. An internal medicine physician and a licensed clinical social worker supervised the program. Surveys were implemented to understand program impacts and career trajectories of the 22 PHCs and health action plans were reviewed over 4 years. In addition, a focus group was conducted with the PHCs using a deductive approach. Results Two years after completing the program, 90.9% of the PHCs were still on the path to health professions programs, 50% had applied to medical school, and 18.2% started medical training. Qualitative impacts on coaches included significant clinical exposure, meaningful connection with patients, ‘bridging’ between the community and health care system and having a more holistic view on health. Patient biomarkers included a decrease in hemoglobin A1c level by 1% point in diabetic patients with diabetes-focused action plans, and smoking-focused action plans led to decreased smoking or cessation. Conclusions The Pre-Medical Health Coach (PHC) program may benefit both PHCs and patients. PHCs were diverse and providing chronic disease self-management support to patients in a safety-net health care system. This program could be readily adapted in health care systems nationwide to increase diverse entrants to the healthcare workforce.